The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2134/agronj2016.12.0734
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community and Succession in Lowland Grasslands under Saline–Alkali Conditions with Grazing Exclusion

Abstract: Core Ideas Soil properties are important factors for pasture degradation in addition to grazing management. Community patch formation could be predicted from soil variables. Community patch types may be used as an indicator of the degree of grassland degradation. Grazing exclusion affects biomass production and species diversity differently. Rangeland degradation poses a serious environmental and economic problem in northern China. This study investigated soil conditions and plant community patches prior to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The soil was classified as chestnut soil (Chinese classification) or a Calcic Luvisol. The primary vegetation is that of a semiarid steppe dominated by perennials, including Leymus secalinus , Potentilla anserine , Artemisia frigida , Salsola collina , Puccinellia florida , Polygonum sibiricum , and Phragmites communis (Zhao, Zhu, Dong, & Li, ).…”
Section: Methodsmentioning
confidence: 99%
“…The soil was classified as chestnut soil (Chinese classification) or a Calcic Luvisol. The primary vegetation is that of a semiarid steppe dominated by perennials, including Leymus secalinus , Potentilla anserine , Artemisia frigida , Salsola collina , Puccinellia florida , Polygonum sibiricum , and Phragmites communis (Zhao, Zhu, Dong, & Li, ).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, grassland degradation is the most frequent, as grassland ecosystems are more sensitive to changes in temperature, precipitation, and soil moisture than other ecosystems [65]. In recent years, under the influence of unfavorable natural factors such as drought, sandstorm, water erosion, salinity, internal helium, groundwater level change, or unreasonable human activities such as overgrazing, over-excavation, indiscriminate cutting and slashing, the grassland utilization performance declined and the grassland ecosystem continued to degenerate [66]. Therefore, the dynamic monitoring and prevention of grassland degradation are the main work content of regional ecological environment protection.…”
Section: Analysis Of High-frequency Abstractmentioning
confidence: 99%
“…The authors' information contained in the collected data allows for the identification of lead authors, as well as their institutions and countries in the field of food security. The h-index refers to the number of published papers that have been cited at least h times [70]. The h-index, total citations, number of publications, and year of first publication in the area of food security for the top 10 influential authors who make the largest contribution to the WoS database are shown in Table 1.…”
Section: Authorsmentioning
confidence: 99%